Characterization of DC magnetron plasma in Ar/Kr/N2 mixture during deposition of (Cr, Al)N coating. (24th January 2017) - Bobzin, K; Bagcivan, N; Theiß, S; Brugnara, R; Bibinov, N; Awakowicz, P
Abstract: Reactive sputter deposition of (Cr, Al)N coatings in DC magnetron plasmas containing Ar/Kr/N2 mixtures is characterized by applying a combination of voltage–current measurement, optical emission spectroscopy (OES) and numerical simulation. Theoretical and experimental methods supplement each other and their combination permits us to obtain the most reliable information about the processes by physical vapor deposition. Gas temperature ( T g ) and plasma parameters, namely electron density n e and electron temperature T e are determined by spatial resolved measurements of molecular nitrogen photoemission. Steady-state densities of Cr and Al atoms are measured using OES. The sputtering of Cr and Al atoms is simulated using the TRIDYN code, measured electric current and applied voltage. Transport of sputtered atoms through the plasma volume is simulated by adopting a Monte-Carlo code. In order to quantify the 'poisoning' of the target surface with nitrogen, simulated steady state densities of Al and Cr atoms at different states of poisoning and at different distances from the target are compared with the measured densities. In addition, simulated fluxes of Cr and Al atoms to the substrate are compared with the measured deposition rates of the (Cr, Al)N coating.